An assessment of the South African longline fishery with emphasis on stock integrity of kingklip, Genypterus capensis (Pisces : ophidiidae) - Japp, David William (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1989)
The South African demersal longline experiment is assessed with emphasis on the target species, kingklip Genypterus capensis. The hypothesis that kingklip on the South African coast comprise a unit stock is tested. Recommendations for the management of the fishery are made. Longlining was found to be commercially viable. Techniques have been developed to target on either kingklip or the Cape hakes, Herluccius capensis and H. paradoxus. Longline fishermen exploit the kingklip spawner stock from August to No v ember by taking advantage of prespawning aggregations on the South-East Coast . Effort switches to the West Coast in late summer and early winter where kingklip are less abundant and a larger proportion of hake is caught. Catch rates of kingklip on the South Coast have declined sharply and the resource there has been exploited at a rate greater than that required to retain 50% of the unexploited biomass . There is a 17,6% probability that the spawner biomass on the South Coast has already been depleted below its pristine level. On the West Coast the catch rates of kingklip are lower than on the South Coast and have not changed significantly, although within the 95% confidence limits there is a possibility that the resource there has also been depleted below 50% of its pristine level. Genypterus capensis on the South African coast comprise a unit stock. Comparison of kingklip morphology using multivariate and discriminant function analysis and of otolith morphology using univariate statistics shows that there are no significant differences between the fish on the West and South Coasts. They are a slow growing species and were aged up to 25 years. Kingklip on the West Coast are smaller and have a lower L~ than those on the South Coast, but this is not a characteristic of discrete stocks. Kingklip on the South Coast mature earlier than those on the West Coast and aggregate to spawn on the South - East Coast in spring. There is no obvious spawning period on the West Coast. It is hypothesized that kingklip spawning on the South-East Coast is in response to favourable environmental conditions that enhances the survival of their eggs and larvae. It is recommended that demersal longlining be established as a permanent kingklip-directed fishery but that effort should not be allowed to increase. The West and South Coasts should be managed .separately. A TAC of 5 OOOt for kingklip should be introduced for 1989 of which 2 OOOt should be allocated to the West Coast and 3 OOOt to the South Coast . A closed season for kingklip from 1 August to 30 September on the South-East Coast is recommended. Hake-directed longlining should not be allowed as its effect on the hake spawner stocks are unknown and could be a potential threat to the stability of the demersal trawl fishery.
Keywords: Genypterus capensis; Ophidiidae; Fisheries -- South Africa; Longlining (Fisheries) -- South Africa